THE INFLUENCE OF NET PROFIT MARGIN AND DEBT TO ASSET RATIO ON STOCK PRICES AT PT BLUE BIRD FOR THE 2011-2023 PERIOD - Lisdawati Lisdawati; Siti Nurcahayati; Adji Widodo; Arif Hidayat (Asosiasi Dosen Muda Indonesia, 2024)
This study aims to determine the influence of Net Profit Margin and Debt to Asset Ratio on the stock price of PT Blue Bird Tbk from 2011 to 2023. A quantitative method was used to analyze these variables both partially and simultaneously, as well as to identify which variable has the most significant impact on the stock price. Based on the data analysis, the results indicate that the Debt to Asset Ratio does not have a significant partial effect on the company’s stock price. Simultaneously, this variable also shows no meaningful impact. The contribution of both variables, Net Profit Margin and Debt to Asset Ratio, to the stock price is 27.7%, while the remaining percentage is influenced by other factors not discussed in this study.